Illumination conditions at the lunar poles: Implications for future exploration. (1st November 2018) - Gläser, P.; Oberst, J.; Neumann, G.A.; Mazarico, E.; Speyerer, E.J.; Robinson, M.S.
Abstract: We produced 400 × 400 km Digital Terrain Models (DTMs) of the lunar poles from Lunar Orbiter Laser Altimeter (LOLA) ranging measurements. To achieve consistent, high-resolution DTMs of 20 m/pixel the individual ranging profiles were adjusted to remove small track-to-track offsets. We used these LOLA-DTMs to simulate illumination conditions at surface level for 50 × 50 km regions centered on the poles. Illumination was derived in one-hour increments from 01 January, 2017 to 01 January, 2037 to cover the lunar precessional cycle of 18.6 years and to determine illumination conditions over several future mission cycles. We identified three regions receiving high levels of illumination at each pole, e.g. the equator-facing crater rims of Hinshelwood, Peary and Whipple for the north pole and the rim of Shackleton crater, and two locations on a ridge between Shackleton and de Gerlache crater for the south pole. Their average illumination levels range from 69.5% to 82.9%, with the highest illumination levels found at the north pole on the rim of Whipple crater. A more detailed study was carried out for these sites as targets for a lander and/or rover equipped with solar arrays. For this purpose we assumed a lander with a structural height of two meters above the ground (height of the solar panels). Here average illumination levels range from 77.1% to 88.0%, with the maximum found at the ridge between Shackleton and de Gerlache crater on the south pole. Distances, sizes and slopes of nearby Permanently Shadowed Regions (PSRs) as a prime science target were also assessed in this case. Highlights: High resolution lunar polar topography based on LOLA. Illumination conditions at the lunar poles. Landing sites in almost continuous illumination near permanently shadowed regions.